(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The Serra Negra territory, which includes 79 archaeological sites, is situated on the northeastern slopes of the Serra do Espinhaço Meridional (Southern Espinhaço Range) in Minas Gerais, Brazil. This article analyzes archaeological data from this region through the lens of landscape theory, contributing to debates surrounding the so-called Archaic Gap. This article engages with the established literature on Holocene occupations of the Brazilian Central Plateau, emphasizing regional particularities. Our findings demonstrate that the Archaic Gap did not occur in Serra Negra, as the territory exhibits evidence of continuous occupation throughout this period. The persistent use and interconnection of landscapes reflect sustained demand, reinforcing the idea of a structured territory during these occupations, in addition to the continuity of social technologies involved in material culture production. Together, contextual, chronological, archaeological, and paleoenvironmental evidence supports the hypothesis of regional stability, both in terms of resources and worldview, marked by enduring site connectivity and occupation. These results further affirm the notion of a structured territory during the Mid-Holocene.